Protective Effects of Thyroid Hormone Deprivation on Progression of Maladaptive Cardiac Hypertrophy and Heart Failure - Kerp, Helena; Hönes, Georg Sebastian; Tolstik, Elen; Hönes-Wendland, Judith; Gassen, Janina; Moeller, Lars Christian; Lorenz, Kristina; Führer, Dagmar (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Thyroid hormones (TH) play a central role for cardiac function. TH influence heart rate and cardiac contractility and altered thyroid function is associated with increased cardiovascular morbidity and mortality. The precise role of TH in onset and progression of heart failure still requires clarification. Methods: Chronic left ventricular pressure overload was induced in mouse hearts by transverse aortic constriction (TAC). One week after TAC, alteration of TH status was induced and the impact on cardiac disease progression was studied longitudinally over 4 weeks in mice with hypo- or hyperthyroidism and was compared to euthyroid TAC controls. Serial assessment was performed for heart function (2D M-mode echocardiography), heart morphology (weight, fibrosis, cardiomyocyte cross-sectional area) and molecular changes in heart tissues (TH target gene expression, apoptosis, mTOR activation) at 2 and 4 weeks. Results: In diseased heart, subsequent TH restriction stopped progression of maladaptive cardiac hypertrophy and improved cardiac function. In contrast and compared to euthyroid TAC controls, increased TH availability after TAC, propelled maladaptive cardiac growth and development of heart failure. This was accompanied by rise in cardiomyocyte apoptosis and mTOR pathway activation. Conclusions: This study shows for the first time a protective effect of TH deprivation against progression of pathological cardiac hypertrophy and development of congestive heart failure in mice with left ventricular pressure overload. Whether this also applies to the human situation needs to be determined in clinical studies and would infer a critical re-thinking of management of TH status in patients with hypertensive heart disease.